TELAAH KRITIS ATAS KONSEP GOOD CORPORATE GOVERNANCE DITINJAU DARI SHARI'ATE ENTERPRISE THEORY - Anis Wulandari; Gugus Irianto; Unti Ludigdo (Faculty of Economics, Universitas Islam Indonesia, 2011)
GCG (Good Corporate Governance) is the most popular principle to keep integrity for organization in the world. Almost all countries in the world keep this principle for building accountability and transparency. Unfortunately, in the practice, GCG has less interpretation about the value of stakeholder. This research is aiming at reconstruction GCG (OECD version) and looking for the more acceptable concept for Islamic values. Hopefully, it can give solution for the problem itself. Having analyzed values and characters of SET, we construct new GCG based on sharia’s values. These values are; first; understanding about stakeholder company more deeply, second; the principle about stakeholder rights; third; the equality about stakeholder behaviour; fourth; principle of transparency;fifth; about accountability of company.